Post COVID 19 resurgence of diphtheria in Kano, Nigeria: analysis of 18,320 casesResearch in context - Muhammad Adamu Abbas; Abubakar Labaran Yusuf; Hassan Adam Murtala; Aisha Adam Abdullahi; Adam Muhammad Murtala; Jordi Bertran Torrelles; Muktar Hassan Aliyu; Hamisu Mohammed Salihu (EBioMedicine, 2025)
Summary: Background: The COVID 19 pandemic led to significant disruptions in health services, including immunisation programs, which contributed to a major post-pandemic diphtheria outbreak in Kano State, Nigeria. This region accounted for 85% of the nation's documented diphtheria cases. Methods: This study examined the epidemiology, clinical characteristics, and mortality outcomes of cases diagnosed between February 2022 and April 2024. Data were collected through the Surveillance Outbreak Response Management and Analysis System (SORMAS), and case definitions followed WHO guidelines. Case fatality rate (CFR) was calculated, and a logistic regression model was used to assess mortality-related risk factors, reporting adjusted odds ratios (AOR). Findings: A total of 18,320 cases were analysed, with the outbreak showing a bimodal distribution. The primary peak occurred in August 2023, followed by a smaller secondary peak in early 2024. The case fatality rate (CFR) was 4.5%. Patients who were not vaccinated had more than double the likelihood of death compared to fully vaccinated individuals (AOR 2.45; 95% CI: 2.05, 2.94, p < 0.0001; logistic regression). Similarly, patients without vaccination documentation also had greater odds, with more than 87% increase likelihood of mortality compared to fully vaccinated individuals (AOR 1.87, 95% CI: 1.27, 2.68, p < 0.0001; logistic regression). Interpretation: Our study reinforces previous reports of the weakening preventive health delivery systems in resource constrained settings, particularly after the disruptions caused by the COVID 19 pandemic leading to the resurgence of vaccine preventable diseases, such as diphtheria. These highlight the need for improved vaccination coverage and surveillance systems. Fundings: This research did not receive any external funding.